Seni Berperang pada Masa Jawa Kuno: Pola Astrologis-Simbolik dalam Naskah Yoga Catur Dewata - Adhi Pradipta, Galang; Made Suparta, I (Jumantara: Jurnal Manuskrip Nusantara, 2024)
Lontar Yoga Catur Dewata (YCD) is a literature in Old Javanese that discusses yoga for starting a war. The art of war is mostly concerned only with war strategy (Griffith 2005; Suryohadiprojo 2008). This study found that the art of war that developed in ancient Java used yoga practices with astrological patterns. YCD manuscripts as research objects are recorded in the FS UI collection with the code AH.58 LT-142 and are now stored in the UI's Library. The text of YCD describes the strategy of war to defeat the enemy personally with astrological-symbolic aspects. It deals with counting days, mantras, yogic practices of the existence of deities in sthana, svaravyanjana-nyasa 'syllabic applause', and animal symbolism. The main formulation of this research problem is how to reveal the narrative of astrological-symbolic patterns and the exposure of the relationship with astrological patterns by the art of war in ancient Java. Research requires philological work to produce text editions from YCD manuscripts. The methods used for data analysis are qualitative descriptive and Pierce's semiotic theory to analyze interpretive signs. The results of this study show that the astrological narrative found in the YCD text is related to warfare strategies in ancient Java. It is a local genius and folk science that developed in the community and is recorded in the YCD text.